Riawati (09030149), The Feasibility Study of Area for The Plants of Melon at Batang Anai District of Padang Pariaman Regency. Thesis. Study Program of Geography STKIP PGRI West Sumatera, Padang - Riawati, Riawati; Hermon, Dedi; Zahara, Leni (Pendidikan Geografi, 2013)
Development of horticulture commodity in the line of fruit sector can be designed as one of the resource to create a new growth in national economic. The development of agribusiness the fruit will be provided an additional value to producer (farmer) and the industry as well as enable to improve the balance of nutrient for costumer, one of them is melon. This research was conducted by having some objective: 1) to know the feasibility characteristic of area for the plants of melon, 2) to know the feasibility of land unit where have the most feasible to develop at Batang Anai District of Padang Pariaman Regency. Technique of taking sample used stratified random sampling, is a drawing technique to a sample which is taken based on strata (level) of each area. The analysis data of this research used descriptive, an analysis in the form of comparative table between area characteristic (organic stuff, rainfall, elevation, air humidity, pH, texture and temperature) compared with the level of feasibility land to the plant of melon. This research need five steps were preparation stage, interpretation, field work, laboratory analysis and post field work. The result of research showed that: 1) there was significant difference of area characters, organic stuff to each land unit and rainfall to each existing land unit at Batang Anai District of Padang Pariaman Regency 2) there was a variation of land feasibility to the plant of melon at Batang Anai District of Padang Pariaman Regency. The land unit with its condition was more feasible to the research area which showed to the fluvial land (F1) with each land unit F1. Qa1.I.Blk.Ai, F1.Aal.I.Kb.A1, F1.Qal.I.Sw.Al, F1. Qai.Tg.Ai, the fluvial land of volcanic area (F2) with the land unit F2.Qal.I.Kb.Al. To the plant of melon was observed in the slope of volcanic area (V2) with the land unit V2.QTt.IV.Kb.Reg, V2.Qal.II.Blk.Reg.